Analisis Pengukuran Kinerja Sumber Daya Manusia Berbasis Balance Scorecard dengan pendekatan Human Resources Scorecard - Nuraini Asriati; Syamsuri Syamsuri (UNIVED Press, 2022)
Human resources are employees or individuals who play an important role in the success of a company. Human resources scorecard is part of the Balanced Scorecard that can be used to measure HR performance. This study aims to analyze the measurement of human resource performance with the Balanced Scorecard method with the human resources scorecard approach at PT. ISM in Pontianak, West Kalimantan Province. The method used in this research is descriptive and cross sectional. The type of data used is primary data, which is obtained from questionnaires containing questions and written statements. The results of the study found that the measurement of human resource performance seen from indicators of work quality, responsibility for work, cooperation with colleagues, orientation to customers, employee initiative and motivation was classified as good. Measurement of HR performance using indicators from the balance scorecard with the human resources scorecard approach, namely learning and growth perspective, internal business process perspective, customer perspective and financial perspective were found in good category. The company's employees are not only qualified in their work, have initiative, are motivated, cooperate, and are customer-oriented in their work, they have also implemented the principles of measuring the balanced scorecard performance with the human resources scorecard approach properly.